2019
DOI: 10.1039/c9cc01300h
|View full text |Cite
|
Sign up to set email alerts
|

Degradation-resistant trehalose analogues block utilization of trehalose by hypervirulent Clostridioides difficile

Abstract: Trehalose analogues designed to resist enzymatic hydrolysis are the first inhibitors of hypervirulence-associated trehalose metabolism in the pathogen Clostridioides difficile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…These findings therefore support the notion that within a nutrient limited environment the degradation of trehalose is required to support mycobacterial growth. Interestingly, recent studies have shown that Clostridioides difficile can efficiently use mannotrehalose (2) as a sole carbon source, 21 highlighting the divergence of trehalose derivative processing pathways that are available in different microorganisms. Moreover, 6-azido-trehalose (4) has previously been found to have very weak antimycobacterial activities and high minimum inhibitory concentrations (MICs) of 100->500 μg mL −1 against Mycobacterium aurum and Mycobacterium tuberculosis 9,22,23 Therefore, we used the resazurin-reduction assay 24 to evaluate the ability of mannotrehalose (2) and galactotrehalose (3) to inhibit the growth of Mtb in liquid media and found that compounds 2-3 did not inhibit the growth of Mtb at concentrations as high as 5 mg mL −1 .…”
Section: Papermentioning
confidence: 99%
“…These findings therefore support the notion that within a nutrient limited environment the degradation of trehalose is required to support mycobacterial growth. Interestingly, recent studies have shown that Clostridioides difficile can efficiently use mannotrehalose (2) as a sole carbon source, 21 highlighting the divergence of trehalose derivative processing pathways that are available in different microorganisms. Moreover, 6-azido-trehalose (4) has previously been found to have very weak antimycobacterial activities and high minimum inhibitory concentrations (MICs) of 100->500 μg mL −1 against Mycobacterium aurum and Mycobacterium tuberculosis 9,22,23 Therefore, we used the resazurin-reduction assay 24 to evaluate the ability of mannotrehalose (2) and galactotrehalose (3) to inhibit the growth of Mtb in liquid media and found that compounds 2-3 did not inhibit the growth of Mtb at concentrations as high as 5 mg mL −1 .…”
Section: Papermentioning
confidence: 99%
“…There is some interest in developing inhibitors of the C. difficile TreA and drugs that target the B. pseudomallei TreA might have clinical utility. Validamycin A is not active against C. difficile TreA [ 78 ] but trehalose derivatives, such as epimers bearing hydroxyl groups at the 2- and 4-positions and also thiotrehalose derivatives, show potential as broader spectrum TreA inhibitors [ 78 ]. The value of any of these drugs for the treatment of specific bacterial diseases awaits investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are validamycin A 35, validoxylamine A 41 36 and trehazolin 35 37, which have IC 50 values in the nanomolar range for porcine kidney trehalase (Figure 4). In contrast, substrate analogues like mannotrehalose 42, 43 38, 5-thiotrehalose 42 39 and 3,3 0 -diketotrehalose 44 40 are mildly potent inhibitors with IC 50 values in the range of 0.1-1 mM (Figure 4). In comparison, as substrate analogue inhibitors, the presented 6-substituted trehaloses 17-a and 19-f have IC 50 values around 9 mM.…”
Section: Discussionmentioning
confidence: 99%